Chemical Modification of Plasticized Lignins Using Reactive Extrusion - Milotskyi, Romain; Szabó, László; Takahashi, Kenji; Bliard, Christophe (Frontiers in Chemistry, 2019)
The reaction of esterification of plasticized Kraft lignin (KL) with succinic and maleic anhydrides using reactive extrusion (REX) was studied in detail. DMSO, glycol and glycerol were found to be efficient plasticizers for lignin. The chemical structure of these new lignin esters was determined using Solid-state 13C CP-MAS NMR and FT-IR analysis. 31P NMR analysis of phosphitylated lignins showed that the aliphatic OH groups of lignin had superior reactivity under the reactive extrusion reaction conditions. The formation of monoesters was confirmed by HSQC NMR spectroscopy. Molecular weight changes after extrusion process were studied using GPC/SEC chromatography. Thermal properties of these polymers were assessed by TGA analysis. The results were compared to lignin esters modified in classical batch conditions. These results show that REX can be used as a new fast, solvent free and continuous process for lignin valorization.